Direct proteomic and high-resolution microscopy biopsy analysis identifies distinct ventricular fates in severe aortic stenosis. (December 2022) - Brandenburg, Sören; Drews, Lena; Schönberger, Hanne-Lea; Jacob, Christoph F.; Paulke, Nora Josefine; Beuthner, Bo E.; Topci, Rodi; Kohl, Tobias; Neuenroth, Lisa; Kutschka, Ingo; Urlaub, Henning; Kück, Fabian; et al.
Abstract: The incidence of aortic valve stenosis (AS), the most common reason for aortic valve replacement (AVR), increases with population ageing. While untreated AS is associated with high mortality, different hemodynamic subtypes range from normal left-ventricular function to severe heart failure. However, the molecular nature underlying four different AS subclasses, suggesting vastly different myocardial fates, is unknown. Here, we used direct proteomic analysis of small left-ventricular biopsies to identify unique protein expression profiles and subtype-specific AS mechanisms. Left-ventricular endomyocardial biopsies were harvested from patients during transcatheter AVR, and inclusion criteria were based on echocardiographic diagnosis of severe AS and guideline-defined AS-subtype classification: 1) normal ejection fraction (EF)/high-gradient; 2) low EF/high-gradient; 3) low EF/low-gradient; and 4) paradoxical low-flow/low-gradient AS. Samples from non-failing donor hearts served as control. We analyzed 25 individual left-ventricular biopsies by data-independent acquisition mass spectrometry (DIA-MS), and 26 biopsies by histomorphology and cardiomyocytes by STimulated Emission Depletion (STED) superresolution microscopy. Notably, DIA-MS reliably detected 2273 proteins throughout each individual left-ventricular biopsy, of which 160 proteins showed significant abundance changes between AS-subtype and non-failing samples including the cardiac ryanodine receptor (RyR2). Hierarchical clustering segregated unique proteotypes that identified three hemodynamic AS-subtypes. Additionally, distinct proteotypes were linked with AS-subtype specific differences in cardiomyocyte hypertrophy. Furthermore, superresolution microscopy of immunolabeled biopsy sections showed subcellular RyR2-cluster fragmentation and disruption of the functionally important association with transverse tubules, which occurred specifically in patients with systolic dysfunction and may hence contribute to depressed left-ventricular function in AS. Graphical abstract: (A) In this study, patients with severe aortic valve stenosis (AS) underwent pre-interventional diagnostic phenotyping including echocardiography prior to (B) transcatheter aortic valve replacement (TAVR), and followed by (C) clinical follow-up. Following the TAVR intervention, LV endomyocardial biopsies were collected for (1) quantitative label-free data-independent acquisition mass spectrometry (DIA-MS) (D-F) and (2) (immuno-)fluorescence labeling (G), confocal microscopy (H), and superresolution stimulated emission depletion (STED) microscopy (I) to identify unique protein expression profiles and subtype-specific AS mechanisms. Proteomic readouts informed about proteins of interest for detailed imaging studies (dashed arrow). (J) Patients with severe AS (aortic valve area (AVA) ≤ 1.0 cm 2 ) were subclassified into one of four hemodynamic subtypes following current guidelines [1, 2 ]: NEF-HG, normal/preserved ejection fraction, high-gradient AS. LEF-HG, low/reduced ejection fraction, high-gradient AS. LEF-LG, low/reduced ejection fraction, low-gradient AS. PLF-LG, paradoxical low-flow, low-gradient AS. Non-failing (NF) donor heart endomyocardial biopsies served as control samples. LVEF, LV ejection fraction; Vmax, aortic valve maximal flow velocity; ΔPm, aortic valve pressure gradient. Unlabelled Image Highlights: LV biopsies were obtained from patients undergoing TAVR to study hemodynamic subtypes in severe aortic stenosis (AS). DIA-MS detected 2273 proteins throughout individual LV biopsies and showed 160 myocardial protein abundance changes. Proteomic profiling segregated AS proteotypes correlating with three hemodynamic subtypes in AS. Histomorphology showed AS subtype-specific differences in cardiomyocyte hypertrophy. Superresolution STED imaging revealed RyR2 cluster fragmentation in AS subtypes with reduced systolic LV function.